Research hotspots and emerging trends in MicroRNA therapy for neuropathic pain: a bibliometric analysis (2009–2024) - Zhang, Yiqiang; Chen, Shushu; Chi, Jiangtao; Gao, Qinghua; Li, Yujie; Wang, Huaizhao; Yu, Yuanyuan (Frontiers in Molecular Neuroscience, 2025)
ObjectiveThis study systematically investigates the evolving trends, research hotspots, and future directions in microRNA-based therapy for neuropathic pain (NP) through bibliometric analysis.MethodsWe extracted literature related to microRNA interventions in NP from the Web of Science Core Collection database, spanning January 2009 to December 2024. A comprehensive analysis was conducted on publication trends, authorship patterns, institutional collaborations, national contributions, journal preferences, co-citation networks, and keyword clusters.ResultsThe final analysis included 250 articles, showing a steady increase in publications over the past 15 years. China was the most productive country, while the United States demonstrated the highest scientific influence. The top three institutions by publication count were Xuzhou Medical University, Nanjing Medical University, and the Chinese Academy of Medical Sciences and Peking Union Medical College. Pain was identified as the most co-cited journal. Keyword analysis revealed “differential expression” with the strongest citation burst intensity, while “peripheral nerve injury,” “mechanical allodynia,” and “proliferation” emerged as recent high-frequency terms.ConclusionIn the field of microRNA therapy for neuropathic pain, investigations into peripheral nerve injury mechanisms, neuroinflammation regulation, and miRNA differential expression patterns have been identified as current research hotspots. Emerging frontiers are now shifting toward three strategic directions: (1) development of targeted delivery systems, (2) precision modulation of nociceptive circuits, and (3) individualized therapeutic strategies. Collectively, miRNAs demonstrate significant potential as innovative NP treatments. While clinical translation of miRNA-based therapies remains a critical research priority, key challenges persist in optimizing target specificity (particularly sequence homology discrimination among miRNA isoforms) and ensuring biocompatibility of delivery platforms.